(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2012)
We all know money rules the world. Hence the economic health is the biggest parameter of the growth of any nation. Similarly economic recessions are dark realities faced by world’s most of the economies whether big or small, grown or growing and even the third world. But the whole world is watching the growth of new economies like China, Russia, India, Brazil, and Mexico. These economies have faced, struggled and survived the recession better than expected by the world. This success is called ‘The Rise of the Rest’ the modern economic phenomenon, and is described by Freed Zakaria in his book ‘The Post - American World’. The rest here means the countries other than America. There are too many questions floating in air, the major one’s are: What is quantum or size of economic recession? How has it affected the various countries around the world? Which countries survived the economic recession the best? What is the status of Indian economy in these turbulent times? This secondary data based research article is an attempt to answer the above major questions and present a clear picture as to why and how India managed to survive the recession of 2008, and later.